The Role of L2 Motivational Self System and Grit in EFL Learners’ Willingness to Communicate: A Study of Public School vs. Private English Language Institute Learners - Ebn-Abbasi, Faramarz; Nushi, Musa; Fattahi, Nazila (Frontiers in Education, 2022)
Learning a second language (L2) is analogous to a journey replete with setbacks and discouragements. Given the pivotal role of communication in L2 learning, researchers have set out to identify factors that may influence L2 learners’ willingness to communicate (L2 WTC). To this end, the present comparative study attempts to investigate the role of the L2 motivational self-system and grit in learners’ L2 WTC in two different educational settings: public schools and private language institutes. L2 motivational self-system includes ideal L2 self (ILS) and ought-to L2self (OLS). Grit also comprises two lower-order constructs: perseverance of effort (POE) and consistency of interest (COI), which are examined separately in this study. The data collected through an online survey from 308 participants were analyzed using the Mann Whitney u-test, Spearman’s rho, and multiple regression analysis. The results revealed a stronger ILS, POE, and a higher level of WTC among language institute learners. In contrast, public school students showed stronger OLS and lower levels of WTC. Moreover, unlike its counterpart, COI did not display a significant correlation or predictive power with/over L2 WTC in either context. The findings suggest that low levels of ILS and lack of POE can lead to lower levels of L2 WTC.